Water resources in Commonwealth of Independent States countries: a literature review - Mukanov, Tynchtyk; Umetaliev, Akylbek; Mambetkulova, Asel; Kaiyrbekov, Almaz; Kannazarova, Zulfiya; Monkayeva, Gulsara; Cservenák, Ákos; Tamás, Péter (Advanced Logistic Systems - Theory and Practice, 2024)
Research on the assessment of water resources in agricultural regions is a prominent area of study. These resources are vital for many arid and agricultural areas, including those in the Commonwealth of Independent States (CIS). This paper provides a comprehensive review of research trends, analyzing scientific production and published articles on water resources in CIS countries from 2000 to 2023. We collected, reviewed, and analyzed 163 publications from the Scopus database meeting our selection criteria. The bibliometric analysis revealed publications in English (149) and Russian (15), annual publication counts, document types, top papers, journals, funding sponsors, subject categories, and affiliations by country and institution. We also examined co-authors and keyword co-occurrence to identify knowledge clusters in the literature. The analysis highlighted the need for international research to enhance scientific exchange on this topic. Long-term, continuous research and sustainable development of water resource concepts are essential for future agricultural and water management integration. This study may inspire new trends in agricultural development, focusing on irrigation efficiency, water distribution, and climate change within a sustainable circular economy.